Pâturage régénératif et bonne gouvernance des parcours face au changement climatique - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
The presentation emphasizes the benefits of regenerative grazing, which offers significant health advantages for pastoral communities, livestock, and the environment. It was delivered by Mounir Louhaichi during the workshop on 'Regenerative Grazing and Good Rangeland Governance in the Face of Climate Change,' held in Douz, Tunisia, on September 11 and 12, 2024